Sudden Unexpected Death and the Mammalian Dive Response: Catastrophic Failure of a Complex Tightly Coupled System - Vincenzi, Frank F. (Frontiers in Physiology, 2019)
In tightly coupled complex systems, when two or more factors or events interact in unanticipated ways, catastrophic failures of high-risk technical systems happen rarely, but quickly. Safety features are commonly built into complex systems to avoid disasters but are often part of the problem. The human body may be considered as a complex tightly coupled system at risk of rare catastrophic failure (sudden unexpected death, SUD) when certain factors or events interact. The mammalian dive response (MDR) is a built-in safety feature of the body that normally conserves oxygen during acute hypoxia. Activation of the MDR is the final pathway to sudden cardiac (SCD) in some cases of sudden infant death syndrome (SIDS), sudden unexpected death in epilepsy (SUDEP), and sudden cardiac death in water (SCDIW, fatal drowning). There is no single cause in any of these death scenarios, but an array of, unanticipated, often unknown, factors or events that activate or interact with the mammalian dive reflex. In any particular case, the relevant risk factors or events might include a combination of genetic, developmental, metabolic, disease, environmental, or operational influences. Determination of a single cause in any of these death scenarios is unlikely. The common thread among these seemingly different death scenarios is activation of the mammalian dive response. The human body is a complex tightly coupled system at risk of rare catastrophic failure when that “safety feature” is activated.